2006
DOI: 10.5194/nhess-6-839-2006
|View full text |Cite
|
Sign up to set email alerts
|

Sediment transport and deposition during extreme sea storm events at the Salerno Bay (Tyrrhenian Sea): comparison of field data with numerical model results

Abstract: Abstract. Seismic stratigraphy and core litho-stratigraphy in the Salerno Bay inner shelf (Southern Tyrrhenian Sea) reveal significant storm deposition episodes over the last 1 ky. Three major events are preserved as decimetre thick silt/sand layers bounded at their base by erosional surfaces and sealed in the muddy marine sequences between 25 and 60 m of depth. Geochronology and chrono-stratigraphy on core sediment point towards a recurrence of major sea storms between 0.1 and 0.3 ky and put the last signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…This work also suggests the absence of any clear relationship between wave size and hydrodynamic state (oscillatory vs. combined flow), highlighting that HCS and SCS can form in both shoreface and shelf settings, but with a continuously decreasing probability of preservation in shallower water (shoreface). This is in agreement with outcrop‐based case studies in both ancient (Dashtgard, Frey, & MacEachern, ; Løseth, Steel, Crabaugh, & Schellpeper, ; Rossi & Steel, ) and modern settings (Budillon, Vicinanza, Ferrante, & Iorio, ; Keen et al, ) that have documented HCS in the shoreface. The lack of mudstone beds and bioturbation is consistent with deposition in a storm‐related, high‐energy depositional environment (MacEachern & Bann, ; Pemberton et al, ).…”
Section: Sedimentary Facies Facies Associations and Depositional Ensupporting
confidence: 88%
“…This work also suggests the absence of any clear relationship between wave size and hydrodynamic state (oscillatory vs. combined flow), highlighting that HCS and SCS can form in both shoreface and shelf settings, but with a continuously decreasing probability of preservation in shallower water (shoreface). This is in agreement with outcrop‐based case studies in both ancient (Dashtgard, Frey, & MacEachern, ; Løseth, Steel, Crabaugh, & Schellpeper, ; Rossi & Steel, ) and modern settings (Budillon, Vicinanza, Ferrante, & Iorio, ; Keen et al, ) that have documented HCS in the shoreface. The lack of mudstone beds and bioturbation is consistent with deposition in a storm‐related, high‐energy depositional environment (MacEachern & Bann, ; Pemberton et al, ).…”
Section: Sedimentary Facies Facies Associations and Depositional Ensupporting
confidence: 88%
“…However, the magnitude of the drop is larger than could be expected, and suggests occurrence of either climate disturbance or variability on time scale larger than the time-span of the available dataset. It should be mentioned that exceptionally severe winter storms were likely to happen during the climatic cooling phase known as Little Ice Age, which occurred from the middle of the 15th century to the 19th century (Lamb, 1979;Budillon et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, an important aspect of changes in the storminess is the impact on the erosion and related coastal vulnerability. Extreme storms can provoke disastrous consequences such as dune destruction (Ferreira et al, 2009), sediment transport beyond the surf zone to unusual depth (Budillon et al, 2006), or burial of benthic biota (Steward et al, 2006). It is reported that changes in storm induced wave action could alter the rates of sediment dynamics and resilience of coastal systems (Regnauld et al, 1999;Sánchez-Arcilla et al, 2000;Lozano et al, 2004).…”
Section: N N Valchev Et Al: Past and Recent Trends In The Western mentioning
confidence: 99%
“…Severe sea storms occur annually during the winter, most coming from the west and southwest, with associated powerful longshore currents that redistribute part of the sediments supplied from the river (Budillon et al, 2005(Budillon et al, , 2006, and references therein).…”
Section: Volturno Rivermentioning
confidence: 99%